Development of information infrastructure in developing countries - Seiful-Mulukov, R. B. ([s.n.] [S.l.], 1985)
Defines a global science and technology information (STI) network. Analyzes state of information and documentation system in groups of countries with different socio-economic levels of development. Highlights the fact of greater information progress in countries where the state orients STI activities to the solution of socio-economic problems. Discusses information types and channels through which they can be obtained. Proposes formation of a global STI network under the auspices of the UN. Outlines extent of Soviet cooperation with developing countries.